Fenomena Alih Kode (Code-Switching) dalam Kelas Bahasa Inggris di Universitas Muhammadiyah: Penelitian - Taslim Taslim; Marsya Putri; Amelia Septiani Putri; Ahmad Nur Fajrin; Ririn Hasrianti; Nurfaidah Tawakkal (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the phenomenon of code-switching in English language learning in the English Language Education Department of Muhammadiyah University of Bone. Code-switching occurs naturally in interactions between lecturers and students in a multilingual context using English, Indonesian, and Buginese. This phenomenon is understood as a communication strategy that plays an important role in supporting material understanding and a smooth learning process. This study uses a qualitative descriptive approach with data collection techniques in the form of classroom observation, semi-structured interviews, and document analysis. The results show that the dominant forms of code-switching are intrasentential and intersentential switching. Code-switching functions pedagogically to explain complex concepts and reduce language anxiety, and socially to build familiarity and affirm cultural identity, thus contributing positively to the English language learning process.